1985
DOI: 10.1128/jcm.22.4.547-552.1985
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay for detection of antibodies to Staphylococcus aureus cell walls in experimental osteomyelitis

Abstract: An enzyme-linked immunosorbent assay was used to evaluate and compare the immunoglobulin G antibody response to Staphylococcus aureus cell walls of rabbits with either chronic staphylococcal osteomyelitis or subcutaneous abscesses. Osteomyelitis of the femur was produced by the intramedullary application of a sclerosing agent (3% sodium tetradecyl sulfate) and S. aureus. Radiographic evidence of osteomyelitis was observed in 10 of the 13 animals that survived the 10-week experimental period, and the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Bone cement was injected through the same opening into the canal to promote the formation of osteomyelitis. Jacob et al [33] reported their model of osteomyelitis on the femur in 1985 according to the method of Norden and Kennedy. Osteomyelitis was caused by intramedullary injection of a sclerosing agent (3% sodium tetradecyl sulfate) and S. aureus (5×106 CFU).…”
Section: Discussionmentioning
confidence: 99%
“…Bone cement was injected through the same opening into the canal to promote the formation of osteomyelitis. Jacob et al [33] reported their model of osteomyelitis on the femur in 1985 according to the method of Norden and Kennedy. Osteomyelitis was caused by intramedullary injection of a sclerosing agent (3% sodium tetradecyl sulfate) and S. aureus (5×106 CFU).…”
Section: Discussionmentioning
confidence: 99%
“…The serological diagnosis of deep-seated S. aureus infections has been the subject of intensive investigation. Whereas earlier assays measured antibodies to extracellular S. aureus, products, notably alpha and gamma hemolysins (13,23), more recently the focus has shifted toward the detection of antibodies to cell-associated components, including TA (8,10,15,25,31,36), PG (2,26,27,30,35), and cell walls (12). These previous studies have shown that significantly elevated levels of antibodies to TA or PG can be detected in the vast majority of patients with complicated S. aureus bacteremia as measured by gel diffusion, ELISA, or radioimmunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…Osteomyelitis model. The method used to create osteomyelitis has been previously described in detail (12). Briefly, the right midfemur of each anesthetized rabbit was exposed surgically, and a duct was created in the medullary cavity with an activated high-speed drill.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation